The Balkans’ Image Constructed in the Public Statements of Donald Trump (2017-2018) - Bratanova, Kalina (Research Papers, 2019)
This piece of research was prompted by the strong academic and scientific interest toward the governance and the rhetorical style of US President Donald Trump, which are not characteristic of a leader of such a rank in American politics. The interest in the specific research topic is also the topicality of political discourse, and in particular its linguistic and pragmatic aspects, in the era of post-truth politics. Of further interest is the negative image of the Balkans, constructed in a diachronic perspective. The results of this paper largely confirm the conclusions made in previous research on Donald Trump’s foreign policy priorities. In a formal aspect, in terms of language and speech patterns, the incumbent US President differs from his predecessors – the presidents of the United States holding office in the post-Cold War period. Yet, in terms of content, Trump’s foreign policy shows some continuity, especially with regard to South-Eastern Europe (SEE) and the Balkans.